Ekoteologi yang melampaui Ajektiva: Pengantar Editor untuk Edisi Khusus - Aruan, Abel K.; Kim, Seoyoung (Asosiasi Teolog Indonesia, 2025)
This editorial introduction explores the distinctive characteristics of doing theology in Asia and the Pacific that should redefine the discourse of ecotheology: not merely a theology qualified as ecological, but one transformed by the earth it names. As a subject matter, too, ecotheology is redefined: not anymore as an item of confession, but as a political theology, that is, an integral part of political life, where nonhumans are also the political subjects. The last section summarizes five contributions to the issue, covering “behavior-regulating” concepts of the Sea, archipelagic everydayness, cash economy, Divine economy, denial/rejection, feel-good theology, Swaraj, Dukkha, and Spirit. The authors hope that the new turn of the field is to be a documentary as well as an alternative to the dualistic, objectifying, and instrumentalizing patterns of thought and behavior; to be genuinely descriptive while remaining committedly normative.